PELESTARIAN TRADISI LISAN DOLA BOLOLO OLEH MASYARAKAT KECAMATAN PULAU HIRI (STUDI KASUS DI SOA DORARI ISA) - Irfan Wahab; Syahril Muhammad; Mukhtar Yusuf (Jurnal GeoCivic, 2023)
The main problem of this research is the erosion of the Dola Bololo oral tradition which is a characteristic of the social life values of the Hiri people, especially in Soa Dorari Isa. The formulation of the problem is (1) How is the preservation of the Dola Bololo oral tradition by the people of Pulau Hiri Subdistrict, (2) What are the values and moral messages contained in the Dola Bololo oral tradition of the people of Hiri Island District, and (3) What are the supporting and inhibiting factors for the preservation the oral tradition of Dola Bololo, the people of Hiri Island District. The purpose of this study was to get an overview of the forms of preservation, values and messages, as well as supporting and inhibiting factors for the preservation of Dola Bololo in Pulau Hiri District. This study used descriptive qualitative method. Located in Soa Dorari Isa. Data was collected using observation, interviews, and documentation. Data analysis used reduction, presentation, and conclusion techniques. The results of the study show that (1) the preservation of the Dola Bololo oral tradition by the Hiri people through (a) traditional ceremonies, (b) rituals, (c) communication of elders, (d) youth communities, and (e) social media; (2) The values and messages in the Dola Bololo oral tradition of the Hiri people are (a) Knowing one's own limits, (b) Learning to let go, (c) Keeping one's speech, (d) Introspective, (e) Understanding the purpose of life; (3) The supporting and inhibiting factors for the preservation of the Dola Bololo oral tradition by the people of Hiri Island District are, (a) The supporting factors are traditional ceremonies, rituals, the youth community; (b) Inhibiting factors are facilities, government, schools, and the community.Keywords: Preservation, Oral Tradition, Dola Bololo